Association between neonatal jaundice and autism spectrum disorders among children: a meta-analysis - Ensiyeh Jenabi; Saeid Bashirian; Salman Khazaei (The Korean Pediatric Society, 2020)
Autism spectrum disorder is a common neurodevelopmental disorder with an unknown etiology. The correlation between neonatal jaundice and the risk of developing autism spectrum disorder was investigated previously. Some studies showed significant associations, whereas others demonstrated no association. In this meta-analysis, we pooled the results of observational studies to examine the association between neonatal jaundice and the risk of autism spectrum disorder among children. We identified all studies published through April 2018 by conducting a literature search using Web of Science, PubMed, and Scopus databases as well as the reference lists of the retrieved studies. The pooled odds ratios (ORs), rate ratio (RR), and their 95% confidence intervals (CIs) were calculated as random effect estimates of association among studies. We conducted a subgroup analysis to explore any potential sources of intergroup heterogeneity. The pooled estimates of OR and RR showed a considerable correlation between neonatal jaundice and ASD among children (OR, 1.35; 95% CI, 1.02-1.68) and (RR, 1.39; 95% CI, 1.05-1.74). A larger effect size was shown in the pooled estimated crude OR than in the adjusted OR (1.75 [0.96-2.54] vs. 1.19 [1.07-1.30]). This study showed that neonatal jaundice may be associated with ASD and may increase the risk of ASD among children.